The Effects Of Collaboration In The Constructivist Web-Based Learning Environment Of An Undergraduate Physics Course. - Atan, Hanafi; Samsudin, Dianne Szalina; M. Idrus, Rozhan (2003)
The effects of the student-facilitator and student-peer collaboration in the constructivist Web-based learning environment of an undergraduate Physics course are reported,